Evolution of Intestinal Microbiota of Asphyxiated Neonates Within 1 Week and Its Relationship With Neural Development at 6 Months - Zhang, Xiaojiao; Liu, Lili; Bai, Wei; Han, Ying; Hou, Xinlin (Frontiers in Pediatrics, 2021)
Objective. To study microbial characteristics of asphyxial neonates within 1 week and research its relationship with neural development at 6 months. Methods. The feces on days 1,3,5 and clinical date of full-time neonates with asphyxia and without asphyxia within period of March 2019 to October 2020 in Peking University First Hospital were collected. Use 16S rDNA Amplicon Sequencing to detect intestinal microbiota of asphyxial neonates and the control group. We follow-up asphyxial neonates to 6 months and use Ages and Stages Questionnaires-3(ASQ-3) to exam development. Results. A total of 45 neonates were enrolled in the study group and 32 neonates in the control group. On day 1, the diversity and richness of microflora of study group were better than that of control group. Non-Metric Multi-Dimensional Scaling analysis showed that significant difference existed in microbiota of the two groups on days 1,3 and 5. At phylum level, the main microflora of the two group had no difference. At genus level, the study group showed increased relative abundance of Clostridium_sensu_stricto_1, Lachnoclostridium, Fusicatenibacter,etc on day 1. On day 3, the relative abundance of Clostridium_sensu_stricto_1,Fusicatenibacter,etc was still more than that of the control group and Staphylococcus was less than that of the control group. On day 5, Clostridium_sensu_stricto_1,Lachnoclostridium were still more than that of the control group and Dubosiella of the study group was obviously increased. At species level, On day 3, the relative abundance of Staphylococcus_caprae of the study group was less than that of the control group. LEfSe analysis showed that microbiota of the study group mainly consist of Lachnospiraceae, Clostridia on day 1 and Clostridia on day 3. In the control group, Staphylococcus was the dominant bacteria on day 3. Neonates of the study group were followed up to 6 months, communication score of ASQ-3 was negatively correlated with the relative abundance of Lachnospiraceae, Clostridia on day 1. Conclusion. The diversity and richness of microbiota of asphyxial neonates on the first day were obviously increased and mainly consist of pathogenic flora. Lachnospiraceae and Clostridia of neonates with asphyxia on day 1 maybe related to neural development at 6 months.